A New Roman Provincial Coin from Pella - Galani, Georgia (Tekmeria, 2019)
The purpose of this article is to present a unique bronze coin of the Roman colony of Pella in Macedonia that was discovered during excavations of the Aristotle University at Dion. The coin belongs to a so-far unpublished issue and bears a female head on the obverse and a standing Pan on the reverse. The article discusses the iconographic types, the denomination and the dating of this issue that does not bear an imperial portrait. A dating in the 3rd century AD is suggested for its production.